In silico structural and functional analysis of phospholipase D from brown recluse spider (Loxoceles reclusa) venom - Afzal, Aqief (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2017.